TRUSTED CONSENT AND RESEARCH BIOBANKS: TOWARDS A ‘NEW ALLIANCE’ BETWEEN RESEARCHERS AND DONORS - Boniolo, Giovanni (Bioethics, 2012)
We argue that, in the case of research biobanks, there is a need to replace the currently used informed consent with trusted consent. Accordingly, we introduce a proposal for the structure of the latter. Further, we discuss some of the issues that can be addressed effectively through our proposal. In particular, we illustrate: i) which research should be authorized by donors; ii) how to regulate access to information; iii) the fundamental role played by a Third Party Authority in assuring compliance with the reciprocal expectations and obligations of donors and scientists. Finally, we briefly analyse two issues that might represent important elements of a ‘new alliance’ between researchers and donors to which the trusted consent could pave the way: i) the correlations between needs and rights of the two parties, and ii) possible economic transactions.